Implications of the Post-2015 Migration Crises for the European Union’s Immigration and Asylum Policies - Tutak, Grzegorz (Roczniki Nauk Społecznych, 2024)
The aim of this paper is to analyze the changes that have been made to the European Union’s immigration and asylum policies after 2015 as a result of the migration crises. The paper poses the following questions: How have the post-2015 migration crises changed the EU’s approach to migration and migration policy? Is the EU, as a community, likely to develop a common comprehensive approach to migration that responds to security challenges? Do these crises affect the EU’s ability to interact with the international environment? On the one hand, the migration crises have demonstrated the weaknesses of the EU’s migration management instruments; on the other hand, they have provided impetus for the development of a new comprehensive approach to migration, embodied in the Pact on Migration and Asylum. Despite the consensus reached on migration, there are still strong convictions within the EU to address migration at the national level.